Modernizing Relationship Therapy through Social Thermoregulation Theory: Evidence, Hypotheses, and Explorations - IJzerman, Hans; Heine, Emma C. E.; Nagel, Saskia K.; Pronk, Tila M. (Frontiers in Psychology, 2017)
In the present article the authors propose to modernize relationship therapy by integrating novel sensor and actuator technologies that can help optimize people’s thermoregulation, especially as they pertain to social contexts. Specifically, they propose to integrate Social Thermoregulation Theory (IJzerman, Coan, et al., 2015a; IJzerman & Hogerzeil, 2017) into Emotionally Focused Therapy by first doing exploratory research during couples’ therapy, followed by Randomized Clinical Trials (RCTs). The authors thus suggest crafting a Social Thermoregulation Therapy as enhancement to existing relationship therapies. The authors outline what is known and not known in terms of social thermoregulatory mechanisms, what kind of data collection and analyses are necessary to better understand social thermoregulatory mechanisms to craft interventions, and stress the need to conduct RCTs prior to implementation. They further warn against too hastily applying these theoretical perspectives. The article concludes by outlining why Social Thermoregulation Therapy is the way forward in improving relationship functioning.